Stabilisasi Tanah Lempung Menggunakan Palm Oil Fuel Ash (POFA) - Charles AN; Ferry Fatnanta; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Clays are soft soil which have a low bearing capacity and potentially to failure. Utilization of additive material is an one way that can be applied to stabilize the clay. This study was conducted to determine the effectiveness of using POFA which is a local available material as an one alternative in stabilizing the clay by increasing its bearing capacity. The research focused on the influence of the POFA percentage with CBR value and the value of Cu in the clay stabilization. The results showed that the increasing of POFA percentage and curing process resulted in the increasing CBR and Cu values. The average increase in the value of CBR curing method 1 to CBR without curing by 0,07% at the top and the bottom of the CBR. whereas for the curing method 2 by 2,29% at the top of CBR and 2,41% at the bottom of CBR. For cu values, the average increase by 1,10 kPa for curing method 1, and 14.65 kPa for curing method 2. It shows an increase in the value of the bearing capacity of the clay. Key Words: CBR value, cu value, clay, POFA.